(untitled) (Castilla. Estudios de Literatura, 2013)
This article takes as its starting point some words which Margaret Atwood pronounced as a tribute after Northrop Frye’s death. Thus the Canadian writer, poet and critic defined Frye’s literary criticism in the following terms: “Because [of] its style, flexibility, and formal elegance, its broad range and systematic structure, his literary criticism takes its place easily within the body of literature itself”. In the present article we analyze those aspects of Frye’s criticism that reinforce its literary basis. In order to illuminate them we suggest contemplating Frye’s literary theory from the point of view of a double vision: that is, a critical writing which can answer the famous question Frye asked in the introduction to Anatomy of Criticism (1957): “What if criticism is a science as well as an art?”. Among those aspects reinforcing the literariness of Frye’s critical writing we focus our attention on the concept of ‘vision’ and on the trope we know as metaphor. Finally, we have considered the role of Canada in Frye’s criticism. Underlying Frye’s criticism on Canada, there is an unresolved tension between the national and the universal. Thus, we have also considered to which extent we can affirm that Frye’s personal biography surfaces his literary criticism, therefore being able to declare that Frye’s poetics (paraphrasing Margaret Atwood) can take its place within the body of (Canadian) literature itself.